Rage with the Machine: When Cyber Troops Oppose the Regime - Fandy Arrifqi (PCD Journal, 2026)
The advent of social media has brought political conversations and activities into the cyber world. One consequence of this is the emergence of cyber troops: special cyber forces that aim to manipulate public opinion on social media. These cyber troops are usually hired by political or economic entities to serve their interests. However, the concept of ludic cybermilitia challenges this, suggesting that cyber troops are not solely controlled by political and economic entities. According to this concept, cyber troops are independent actors engaged in a form of privatised violence. This study builds on findings relating to the hashtags #SaveKIPKuliah and #SavePulauGebe, which oppose political and economic actors. Similarities in content and posting patterns between the tweets suggest that the two hashtags represent coordinated attacks. Based on these findings, the study proposes that cyber troops may also resist political and economic actors through privatised violence.